Naquib al-Attas Educational Thought in Contemporary Islamic Education - Enjang Sukandi; Siti Nia Anisa Inayah (al-Afkar, Journal For Islamic Studies, 2024)
Based on the discussion above, it can be concluded that Muhammad Naquib al-Attas' educational thinking tends to be selective reconstructive in nature which seeks to present an integrated Islamic education system, which still maintains the principle of harmony and individual balance which describes the realization of the main human function as ‘abd Allah and caliph al ard. According to al-Attas, science today has been contaminated by thoughts from the secular Western world that are contrary to the values of Islamic teachings. Therefore, it is necessary to make an effort through the “Islamization of science” movement by taking positive aspects from modern developments as selectively as possible, even though they come from the West.